Mosaicos reprodutivos e morfometria de estômatos em Eriotheca gracilipes (Bombacoideae-Malvaceae) - Serra, Annelise da Cruz (2018)
The geographical distribution of embryonic patterns found in Eriotheca is still poorly understood. However, it is known that the distribution of Cerrado species, as well as their phytophysiognomies and biogeography, are the result of paleoclimatic fluctuations and have determined the evolutionary course of the species of this biome. Eriotheca gracilipes (Malvaceae - Bombacoideae), a species with wide distribution in the Cerrado, exhibit reproductive and cytological mosaics with polyembryonic individuals being polyploid and apomictic, and monoembryonic being diploid and sexual. A wide mapping of the patterns found in these populations could help to understand how the dispersal of this species occurred and reveal areas of refuge that may have occurred during periods of paleoclimatic fluctuations. The definition of each embryonic pattern found in species that exhibit these reproductive mosaics is time consuming and can be a laborious tool. Therefore, in chapter 1, we verified the possible relationship between stomata size and embryonic pattern in order to test the efficiency of morphometric data in the detection of such reproductive patterns. For this study, it were collected 25 populations of E. Gracilipes throughout the Savanna Cerrado in order to measure the width and hight of the stomata, obtained by using the decal technique. Six populations were identified as monoembrionic, eleven as polyembrionic and two presented low frequency of polyembrionics. Other six populations were classified as being undefined. We could see that geographic (latitude, altitude, longitude) and cytological factors act together with the embriony pattern in the determination of stomata size and, therefore, this simple and direct relationship between morphometry and reproduction system could not be established. In spite of that, a certain geographic division was showed by the embryonic patterns, which allowed us to make some inferences about how occurred the distribution and dispersal of these populations. Monoembryonic populations presented, in general, smaller size of stomata and are associated with higher altitudes in addition to its wide distribution. In a second chapter we tested the viability of cross-pollination between different ploidies of E. gracilipes (2x and 6x) which resulted in only one hybrid individual. It were analyzed by flow cytometry, 397 seedlings of different populations of Eriotheca with caryotypes well known so we could compair the genomic size of the individuals with the mother plants. Aside that, stomata from the seedlings and from the hybrid individual were measured for comparison to each genomic size. It were analyzed 50 stomata of three seedlings obtained from each mother plant and 80 of the hybrid individual. The results confirmed that the ploidy showed by the Eriotheca species considered in the study does influence the stomatal size of the individuals. However, the hybrid individual did not show such a clear relationship between stomatal morphometry and its level of ploidy. Nevertheless, the study on hybrid individuals can enlighten the behavior of populations whose stomatal size does not follow the expected pattern when considering the species reproductive and cytological mosaics.